2013
DOI: 10.1128/aem.00443-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aerated Steam Treatment of Alfalfa and Mung Bean Seeds To Eliminate High Levels of Escherichia coli O157:H7 and O178:H12, Salmonella enterica, and Listeria monocytogenes

Abstract: Sprouts contaminated with human pathogens are able to cause food-borne diseases due to the favorable growth conditions for bacteria during germination and because of minimal processing steps prior to consumption. We have investigated the potential of hot humid air, i.e., aerated steam, to treat alfalfa and mung bean seeds which have been artificially contaminated with Escherichia coli O157:H7, Salmonella enterica subsp. enterica serovar Weltevreden, and Listeria monocytogenes Scott A. In addition, a recently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(40 reference statements)
0
9
0
2
Order By: Relevance
“…Desiccated strains of E. coli and Salmonella are characterized by extreme resistance to physical and chemical stressors including heat (Beuchat and Scouten, 2002; Beuchat et al, 2013; Studer et al, 2013; Syamaladevi et al, 2016). Parameters for the heat inactivation of dry bacterial cells are comparable to the moist heat inactivation of bacterial endospores spores rather than pasteurization (Brandl et al, 2008; Du et al, 2010; Podolak et al, 2010).…”
Section: Heat Resistance Of Desiccated E Colimentioning
confidence: 99%
“…Desiccated strains of E. coli and Salmonella are characterized by extreme resistance to physical and chemical stressors including heat (Beuchat and Scouten, 2002; Beuchat et al, 2013; Studer et al, 2013; Syamaladevi et al, 2016). Parameters for the heat inactivation of dry bacterial cells are comparable to the moist heat inactivation of bacterial endospores spores rather than pasteurization (Brandl et al, 2008; Du et al, 2010; Podolak et al, 2010).…”
Section: Heat Resistance Of Desiccated E Colimentioning
confidence: 99%
“…They did not monitor surviving Listeria on treated cantaloupe during postexposure storage, but reported that treated whole melons and cut pieces displayed no indications of decay or color change upon storage at 5 °C. Exposure to aerated steam at an average temperature of 70 °C for a 300 s reduced L. monocytogenes on mung bean and alfalfa seeds by 4 and 5 log 10 , respectively, without significantly impacting germination (Studer et al., ). Lastly, superheated steam (200 °C, 15 s) was reported to achieve >5 log 10 reductions in L. monocytogenes on almond and pistachio nuts without any accompanying quality changes (Ban & Kang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Neither group reported upon survivor outgrowth (that is, storage studies), but Studer et al. () were able to recover L. monocytogenes from steam‐treated alfalfa seeds via culture enrichment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is increased consumption caused by enhanced recognition by the broader public of sprouts as nutritious food. However, during mass production thereof, favourable conditions are generated during germination for bacteria such as Salmonella spp., especially when hygienic standards are not followed (Studer et al, 2013). In Europe, outbreaks linked to contaminated sprouts were caused by S. enterica subsp.…”
Section: Introductionmentioning
confidence: 99%